2009
DOI: 10.1051/0004-6361/200811276
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of cosmic shear covariances on cosmology

Abstract: Context. In cosmic shear likelihood analyses, the covariance is most commonly assumed to be constant in parameter space. Therefore, when calculating the covariance matrix (analytically or from simulations), its underlying cosmology should not influence the likelihood contours. Aims. We examine whether the aforementioned assumptions hold and quantify how strong cosmic shear covariances vary within a reasonable parameter range. Furthermore, we examine the impact on likelihood contours when assuming different cos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
136
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 128 publications
(142 citation statements)
references
References 23 publications
6
136
0
Order By: Relevance
“…The covariances used in our likelihood analysis are calculated from the power spectrum P E as described in , assuming our fiducial cosmology. This method does not account for the non-Gaussianity of the shear field or the cosmology-dependence of the covariance (Eifler et al 2009), however these issues are not crucial for our purpose as we are only interested in the relative performance of COSEBIs and the 2PCFs. More important is that we can choose an arbitrary binning in the 2PCF covariance.…”
Section: Model Choicementioning
confidence: 99%
“…The covariances used in our likelihood analysis are calculated from the power spectrum P E as described in , assuming our fiducial cosmology. This method does not account for the non-Gaussianity of the shear field or the cosmology-dependence of the covariance (Eifler et al 2009), however these issues are not crucial for our purpose as we are only interested in the relative performance of COSEBIs and the 2PCFs. More important is that we can choose an arbitrary binning in the 2PCF covariance.…”
Section: Model Choicementioning
confidence: 99%
“…Since an additional cosmology dependence would lead to tighter constraints, this is a conservative assumption (see e.g. Eifler et al 2009). Using the equivalence of the Fisher matrices, and returning to the notation in the context of the nulling technique, we then arrive from (25) at the following expression for the original (index "orig") and the nulled (index "null") data vector (see Appendix.…”
Section: Fisher Matrix Formalismmentioning
confidence: 99%
“…This non-Gaussian contribution is described by the trispectrum or the Fourier transform of the 4-point correlation function. Cooray & Hu (2001) used the halo model to estimate the trispectrum contribution and showed that the non-Gaussian errors do degrade the precision of cosmological parameter determination, and therefore cannot be ignored for planned future surveys (see also Takada & Jain 2008;Eifler, Schneider & Hartlap 2008). Also recently, Smith (2008) studied the covariance matrix of the halo power spectrum using numerical simulations.…”
Section: Introductionmentioning
confidence: 99%